1989
DOI: 10.1016/0304-3959(89)90108-5
|View full text |Cite
|
Sign up to set email alerts
|

Central post-stroke pain — a controlled trial of amitriptyline and carbamazepine

Abstract: A double-blind, 3-phase, cross-over, placebo-controlled trial of the pain-relieving effect of amitriptyline and carbamazepine was carried out in 15 patients with central post-stroke pain (CPSP) but without signs of depression. Treatment was given, in randomized order, for periods of 4 weeks, separated by 1 week wash-out. The final doses were 75 and 800 mg/day, respectively, for amitriptyline and carbamazepine. The treatment effects were assessed by daily ratings of pain intensity on a 10-step verbal scale and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
159
0
14

Year Published

1996
1996
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 353 publications
(176 citation statements)
references
References 38 publications
3
159
0
14
Order By: Relevance
“…In a placebocontrolled study of post-stroke pain, carbamazepine was shown to be more effective than placebo but equivalent to amitriptyline. 103 These studies, however, are small and less rigorous than those conducted with today's standards.…”
Section: Carbamazepinementioning
confidence: 99%
“…In a placebocontrolled study of post-stroke pain, carbamazepine was shown to be more effective than placebo but equivalent to amitriptyline. 103 These studies, however, are small and less rigorous than those conducted with today's standards.…”
Section: Carbamazepinementioning
confidence: 99%
“…More recently, amitriptyline has been shown, in a double-bLld trial, to be effective in central post-stroke pain. 32 In CPSP, there is evidence that the earlier antidepressant therapy is started, the more effective it is. 7 The difficulty with many conditions causing spinal pain, as with cerebral stroke, is that the pain frequently does not come on until some time after the insult has occurred, or begun.…”
Section: Treatmentmentioning
confidence: 99%
“…In the clinic, CPSP is usually treated with adjuvant analgesics, such as antidepressants, antiepileptogenics and narcotic analgesics, based on the treatment of neuropathic pain or surgery. 4,[9][10][11][12] However, the effect of adjuvant analgesics on the BCAO-induced pain is unclear.…”
mentioning
confidence: 99%